Analisis Penerapan Green Accounting dan Corporate Social Responsibility Terhadap Nilai Perusahaan Melalui Kemampulabaan - Salsabila, Adinda; Sari, Shinta Permata (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The stakeholders expect that the firm's value will increase supported by increased profitability. This study aims to examine the impact of green accounting and corporate social responsibility on firm value with profitability as an intervening variable. This study uses quantitative methods with SPSS data analysis, involving 57 samples. The sample are basic material sector companies listed on the Indonesia Stock Exchange, with a research period from 2021 to 2023. The results show that only the direct relationship between profitability and firm value has a positive impact on corporate social responsibility, while the direct relationship between green accounting and corporate social responsibility does not impact firm value. The results also show that the relationship between green accounting and corporate social responsibility on firm value with the mediating variable of profitability does not an impact. This study also gives opportunities for further study of other factors that may affect the relationship between green accounting, corporate social responsibility, firm value, and profitability.